2020
DOI: 10.3390/ijerph17114114
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Underlying Causes of Chinese Eastern Star, Korean Sewol, and Thai Phoenix Ferry Accidents by Employing the HFACS-MA

Abstract: Maritime safety is a significant topic in the maritime industry since the numerous dangers at sea could lead to loss of property, environmental pollution, and even casualties. Existing research illustrates that human factors are the primary reasons of maritime accidents. Indeed, numerous maritime accidents can be classified into different types of human factors. In this context, the Human Factors Analysis and Classification System for Maritime Accidents (HFACS-MA) model is introduced in this paper. The HFACS-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
0
9
0
3
Order By: Relevance
“…Further research on the subject has shown that uncorrected issues, cognitive errors, and lack of situational awareness can lead to poor mental states (Yıldırım et al, 2019). Wang et al (2020), using the HFACS‐MA model, investigated the accidents of the Eastern Star in China, the Sewol in South Korea, and the Phoenix Ferry in Thailand. They found that organizational process deficiencies were critical contributing factors in these three accidents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research on the subject has shown that uncorrected issues, cognitive errors, and lack of situational awareness can lead to poor mental states (Yıldırım et al, 2019). Wang et al (2020), using the HFACS‐MA model, investigated the accidents of the Eastern Star in China, the Sewol in South Korea, and the Phoenix Ferry in Thailand. They found that organizational process deficiencies were critical contributing factors in these three accidents.…”
Section: Discussionmentioning
confidence: 99%
“…found that inadequate operating procedures led train drivers to believe that they were being supervised and controlled by station operators responsible for the dispatching of track sections, resulting in unsafe train control. Further research on the subject has shown that uncorrected issues, cognitive errors, and lack of situational awareness can lead to poor mental states(Yıldırım et al, 2019) Wang et al (2020),. using the HFACS-MA model, investigated the accidents of the Eastern Star in China, the Sewol in South Korea, and the Phoenix Ferry in Thailand.…”
mentioning
confidence: 99%
“…In China between 2008 and 2019, there was an increase in ship cargo and passenger capacity but a decrease in the number of transportation ships, indicating that the size of the ships increased in China. According to the regulations of the CMSRC and International Maritime Organization, ships >25 m in length must be equipped with an automatic identification system, vessel traffic services (VTS), and modern navigational devices to provide related information and real-time data (20)(21)(22)(23)(24)(25). VTS and other navigation services, as well as better ship design, can improve the safety and efficiency of ship traffic through monitoring of the ship's position, course, speed, and identity for better navigation in the appropriate watercourse and therefore reduce the risk of ship collisions (24,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…The Sewol disaster serves as a poignant example, alongside the Le Joola ferry § § tragedy in Senegal, where over 1,800 passengers perished, making it the second-worst maritime disaster of the modern era and the highest death toll of any African maritime sinking (Rothe et al, 2006). Despite passing safety inspections before these accidents, both incidents revealed critical governance shortcomings (Wang et al, 2020). This necessitates essentially strengthening governance structures and practices to enhance safety in the DF sector.…”
Section: Governancementioning
confidence: 99%